Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/jmcb/mjx025
|View full text |Cite
|
Sign up to set email alerts
|

TFIIA transcriptional activity is controlled by a ‘cleave-and-run’ Exportin-1/Taspase 1-switch

Abstract: Transcription factor TFIIA is controlled by complex regulatory networks including proteolysis by the protease Taspase 1, though the full impact of cleavage remains elusive. Here, we demonstrate that in contrast to the general assumption, de novo produced TFIIA is rapidly confined to the cytoplasm via an evolutionary conserved nuclear export signal (NES, amino acids 21VINDVRDIFL30), interacting with the nuclear export receptor Exportin-1/chromosomal region maintenance 1 (Crm1). Chemical export inhibition or gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…As regulators of many biological processes, proteases are essential for cell viability, and their deregulation is often associated with various pathologies including cancer. , In particular, the unique threonine protease Taspase 1 (threonine aspartase 1) is not only involved in regular cellular development but also responsible for the progression of leukemias and solid tumors. In the group of threonine proteases, only Taspase 1 is able to cleave other substrates in trans by recognizing a conserved Q 3 [FILV] 2 D 1 ↓G 1 X 2’ D 3’ D 4’ motif. Thus, Taspase 1 is an endopeptidase that utilizes the N-terminal threonine (Thr 234 ) of its mature β-subunit as the active site. Besides the mixed-lineage leukemia protein (MLL), the general transcription factor IIA (TFIIA) , and the upstream stimulatory factor 2 (USF2) could all be identified as Taspase 1 target proteins . Importantly, Taspase 1 is preferentially expressed during embryonic development, and thus, pharmacological intervention should not affect healthy adult cells. ,, In contrast, tumor cells have been demonstrated to upregulate the expression of Taspase 1 to promote their proliferation and counteract apoptotic cell death. ,,, This classifies Taspase 1 as a ″non-oncogene addiction″ protease. , However, the full repertoire of physiological and pathological targets and pathways affected by Taspase 1 is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As regulators of many biological processes, proteases are essential for cell viability, and their deregulation is often associated with various pathologies including cancer. , In particular, the unique threonine protease Taspase 1 (threonine aspartase 1) is not only involved in regular cellular development but also responsible for the progression of leukemias and solid tumors. In the group of threonine proteases, only Taspase 1 is able to cleave other substrates in trans by recognizing a conserved Q 3 [FILV] 2 D 1 ↓G 1 X 2’ D 3’ D 4’ motif. Thus, Taspase 1 is an endopeptidase that utilizes the N-terminal threonine (Thr 234 ) of its mature β-subunit as the active site. Besides the mixed-lineage leukemia protein (MLL), the general transcription factor IIA (TFIIA) , and the upstream stimulatory factor 2 (USF2) could all be identified as Taspase 1 target proteins . Importantly, Taspase 1 is preferentially expressed during embryonic development, and thus, pharmacological intervention should not affect healthy adult cells. ,, In contrast, tumor cells have been demonstrated to upregulate the expression of Taspase 1 to promote their proliferation and counteract apoptotic cell death. ,,, This classifies Taspase 1 as a ″non-oncogene addiction″ protease. , However, the full repertoire of physiological and pathological targets and pathways affected by Taspase 1 is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…S21†), a plethora of NLSs have been identified in many cancer-/disease-relevant proteins, such as p53, NPM, TFIIA, or the superfamily of nuclear receptors, with the vast majority classified as monopartite signals. 19,30,66–68…”
Section: Resultsmentioning
confidence: 99%
“…S21 †), a plethora of NLSs have been identied in many cancer-/ disease-relevant proteins, such as p53, NPM, TFIIA, or the superfamily of nuclear receptors, with the vast majority classi-ed as monopartite signals. 19,30,[66][67][68] However, recent studies revealed that the traditional denition of bipartite NLSs might be too restrictive and linker length can vary within a broader range. 69 As such, extension of the surface-exposed, importin-interacting amino acid residues of NLSs initially classied as monopartite might render them amenable to analogous interference strategies.…”
Section: Dual Inhibition In Vivo: 11d Suppresses Taspase 1 Function A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of Taspase1's verified target proteins such as USF2 [1] and TFIIA [6,58] have been annotated as estrogen-regulated genes, as well as the known Taspase1 interaction partner Nucleophosmin1 (NPM1). MLL proteins, the most prominent Taspase1 substrates, interact with hormone receptors (NR) and are involved in steroid-hormone induced transcriptional activation [22,59].…”
Section: Taspase1 Interacts With Diverse Players Of the Cellular Estr...mentioning
confidence: 99%